2022
DOI: 10.1002/jnr.25033
|View full text |Cite
|
Sign up to set email alerts
|

The key roles of organelles and ferroptosis in Alzheimerʼs disease

Abstract: Alzheimerʼs disease (AD), an age-related neurodegenerative disease, is a striking global health problem. Ferroptosis is a newly discovered form of cell death characterized by iron-dependent lipid peroxidation products and the accumulation of lethal reactive oxygen species. Strict regulation of iron metabolism is essential to ensure neuronal homeostasis. Excess and deficiency of iron are both associated with neurodegeneration.Studies have shown that oxidative stress caused by cerebral iron metabolism disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 293 publications
(334 reference statements)
0
6
0
Order By: Relevance
“…PI3K/AKT is a key regulator of cell behaviors such as apoptosis, proliferation and differentiation [49]. In particular, it plays a neuroprotective role in diseases of the central nervous system, such as Alzheimer's disease (AD) [50,51], Parkinson disease (PD) [52,53], IS [54,55], and ICH [56][57][58]. Studies of Bao Yu [59] and Han Cai Ping [60] have shown that PI3K and P-AKT protein expression will show an increase in 6 h after the mouse ICH is made.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT is a key regulator of cell behaviors such as apoptosis, proliferation and differentiation [49]. In particular, it plays a neuroprotective role in diseases of the central nervous system, such as Alzheimer's disease (AD) [50,51], Parkinson disease (PD) [52,53], IS [54,55], and ICH [56][57][58]. Studies of Bao Yu [59] and Han Cai Ping [60] have shown that PI3K and P-AKT protein expression will show an increase in 6 h after the mouse ICH is made.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cystine deprivation was implicated in ferroptosis, a novel iron-dependent form of regulated cell death that is driven by excessive oxidative damage to lipids [53]. Although the relationship between ferroptosis and POI has not been clarified, the accumulated evidence indicates that ferroptosis contributes to the major complications of POI, including cardiovascular disease [54], neurodegenerative disease [55], and osteoporosis [56]. According to a recent report published in Science, cystine also acts as a key regulator in diet-regulated growth suppression programs, such as autophagy [57], which is critical for ovarian function and participates in the pathogenesis of POI [58].…”
Section: Discussionmentioning
confidence: 99%
“…The Golgi apparatus is essential for the synthesis and modification of proteins and lipids, and Golgi fragmentation has been observed in AD 52 . Golgi fragmentation is suggested to promote neuronal ion channel damage and the accumulation of tau and Aβ 53 . Specialized regions of plasma membranes, such as caveolae, modulate reactive oxygen species (ROS) producing systems 54 .…”
Section: Discussionmentioning
confidence: 99%